The evolution of occupational profiles of information professionals - Abadal, Ernest; Rubió, Anna (Anuario ThinkEPI, 2017)
The evolution of the job market for information professionals within the last several years is categorized into three concentric layers: core, envelope, and horizon. This overview is complemented by the analysis of job offers managed by the Faculty of Library and Information Science's Job Offers Information Service (SIOF) of the University of Barcelona in the 2015-16 academic year and it is also compared with the data of the 2009-2010 academic year. There have been significant variations in the job providers side (evolving from public to private sectors) and in the most demanded profiles (from the traditional library core to new emerging functions). Finally, some implications of these changes for universities, associations, and professionals are explained.
Keywords: Professional profiles; Employment offers; Job market; Job Offers Information Service; SIOF.